Mayday! Mayday! Mayday! Saving Companies in Financial Distress - Sharija Che Shaari; Ida Shafinaz Mohamed Kamil; Junaidah Zeno (Penerbit UMS, 2021)
Amid mounting concerns about the Coronavirus (COVID-19) pandemic, economies all over the world are facing an unprecedented economic slowdown, and Malaysian companies are not spared. Even companies with sound underlying operations cannot generate sufficient revenues or income thus making it unable to meet or pay its financial obligations as they become due. The pandemic slowdown is still nowhere in sight; the companies will plunge farther in debt with little or no revenue generated which might have resulted in closing the business entirely. However, liquidation should only be the last resort upon the exhaustion of rescue mechanisms which can either be a formal or informal process. The latter process is not within the ambit of this article. The aim of this article is to enlighten the rescue mechanisms in saving distressed companies provided by the Companies Act 2016, namely, scheme of arrangement, corporate voluntary arrangement, and judicial management. This study uses the legal doctrinal methodology by analysing the Companies Act 2016 and decided cases, scholarly articles, legal reports, and legal briefs. The discussion will highlight the practical issues faced in each mechanism. A question is raised, whether the mechanisms reflect the notion of rescue culture? It is, therefore, pertinent for the distressed companies to consider the options best suited them to rescue their businesses that will overcome their financial problems and avoid liquidation. This study will also add to the corpus of corporate legal literature of Malaysia.